Surface Microhardness of Bulk-Fill Resin Composites Handled With Gloves - Berto-Inga, Julissa (2023)
Aim: It has been reported that resin composites may experience alterations in their mechanical properties when they come into contact with glove powder. Therefore, the present study aimed to compare the surface microhardness of 3 bulk-fill resin composites handled with latex and nitrile gloves prior to light curing. Methods: This in vitro experimental study consisted of 90 resin composite specimens with a 6-mm diameter and a 4-mm height divided equally and randomly into 9 groups. Prior to light curing, the resin composites were handled with latex gloves, nitrile gloves, or only a spatula (control). Subsequently, the surface microhardness was measured with an Electronic Vickers Hardness Tester. The Kruskal–Wallis nonparametric H test with Bonferroni correction was used for comparisons. A significance level of 5% (P < .05) was considered. Results: When comparing surface microhardness of each resin composite according to type of handling received, significant differences were observed in Filtek One Bulk Fill (P < .001) and Opus Bulk Fill (P < .001). In addition, these resin composites presented significantly higher surface microhardness than Tetric N-Ceram Bulk Fill resin (P < .05) when handled with latex gloves, nitrile gloves, and only a spatula. Finally, Filtek Bulk Fill resin presented significantly higher surface microhardness compared to Opus Bulk Fill resin when handled with nitrile gloves (P = .038) and a spatula only (P = .033). Conclusions: The surface microhardness of Filtek One Bulk Fill and Opus Bulk Fill resin composites decreased significantly when handled with latex or nitrile gloves, showing no variation in Tetric N-Ceram Bulk Fill resin composite. In addition, Filtek One Bulk Fill resin composite showed significantly higher surface microhardness than Opus Bulk Fill and Tetric N-Ceram Bulk Fill resin composites when handled with nitrile gloves. It is recommended that bulk-fill resin composites be handled with a spatula, because the use of latex or nitrile gloves could adversely affect their clinical performance.